CONTRIBUTIONS OF PSYCHOLOGY IN CHILDHOOD GRIEF WITH THE LOSS OF A PARENT - Paula Carvalho Silva, Ana; Thalissa Diniz Maranhão Oliveira, Mara; de Cássia da Silva Ferreira, Yasmin; Carmo Ferreira da Silva, Luciana (Revista Gênero e Interdisciplinaridade, 2023)
Grief is a process experienced by the loss or absence of a person, object or situation, triggering suffering, in addition to behavioral, emotional and sentimental reactions. According to studies, the child has the ability to understand about death, only needing to respect their level of cognitive/emotional development. The parents represent physical, emotional and security support for the infant, thus, their departure is understood as causing extreme pain and generating feelings of hopelessness and helplessness. Psychology has several strategies to deal with childhood grief. This work aimed to demonstrate the contribution of Psychology in the face of grief in childhood with the loss of one of the parents, through the understanding of child development, the understanding of grief in childhood, the importance of mourning and psychological assessment the loss of one of the parents. It was based on a bibliographic review with a qualitative-descriptive approach, in the period between 2005 and 2021. It concluded the importance of psychology for the elaboration of child mourning, given that this science has several means, such as psychoeducation about mourning and the emotions triggered by it, ludic therapy, participation in centers or support groups by the surviving parent, as well as psychotherapy to redefine this process and its consequences.